Digital scanned laser light-sheet fluorescence microscopy (DSLM) of zebrafish and drosophila embryonic development - Keller, Philipp J.; Schmidt, Annette D.; Wittbrodt, Joachim; Stelzer, Ernst H. K. (Cold Spring Harbor protocols, 2011)
Embryonic development is one of the most complex processes encountered in biology. In vertebrates and higher invertebrates, a single cell transforms into a fully functional organism comprising several tens of thousands of cells, arranged in tissues and organs that perform impressive tasks. In vivo observation of this biological process at high spatiotemporal resolution and over long periods of time is crucial for quantitative developmental biology. Importantly, such recordings must be realized without compromising the physiological development of the specimen. In digital scanned laser light-sheet fluorescence microscopy (DSLM), a specimen is rapidly scanned with a thin sheet of light while fluorescence is recorded perpendicular to the axis of illumination with a camera. Combining light-sheet technology and fast laser scanning, DSLM delivers quantitative data for entire embryos at high spatiotemporal resolution. Compared with confocal and two-photon fluorescence microscopy, DSLM exposes the embryo to at least three orders of magnitude less light energy, but still provides up to 50 times faster imaging speeds and a 10-100-fold higher signal-to-noise ratio. By using automated image processing algorithms, DSLM images of embryogenesis can be converted into a digital representation. These digital embryos permit following cells as a function of time, revealing cell fate as well as cell origin. By means of such analyses, developmental building plans of tissues and organs can be determined in a whole-embryo context. This article presents a sample preparation and imaging protocol for studying the development of whole zebrafish and Drosophila embryos using DSLM.